Our Experience in Chordee without Hypospadias: Results of 102 Cases - Polat, Emre Can; Erdem, Mehmet Remzi; Topaktas, Ramazan; Ersoz, Cevper; Onol, Sinasi Yavuz (Urology Journal, 2014)
Purpose: We present long-term surgical experience of 102 chordee without hypospadias cases. Materials and Methods: This retrospective study included 102 chordee without hypospadias cases who were surgically treated between 1999 and 2012. Range of patients' age was from 1 month to 31 years. Seventy-two patients were adult, and 30 were children. Mean duration of follow up was 49.3 months. The patients were categorized into 4 groups including skin tethering (group 1), fibrotic dartos and Buck's fasciae ( group 2), corporeal disproportion ( group 3) and urethral tethering (group 4) with the aid of intraoperative artificial erection, according to the structural defect. Results: Forty patients (group 1) were successfully treated with penile degloving. Except 3 (10%) of 31 (group 2) cases, extensive resection of the fibrotic dartos and Buck's fascia was needed to straighten the penis. Corporeal disproportion was identified in 27 patients of whom 2 cases (7%) had complications. One of them developed urethrocutaneous fistula, and he was treated with buccal mucosal graft urethroplasty successfully. In other one, chordee persisted after two years, and we had to do Nesbit wedge resection after tunica albuginea plication to achieve penile straightening at the same session; otherwise we avoid tunica albuginea excision or incision. Overall 96 (94%) of 102 patients were successfully treated at first operation. Conclusion: We concluded that tunica albuginea plication is very effective for both prepubertal and postpubertal period and also in management of recurrence. We believe that, in experienced hands, early surgical correction can be done successfully in this condition.